Cross-Lagged Associations Between Children's Stress and Adiposity. Issue 1 (January 2015) - Michels, Nathalie; Sioen, Isabelle; Boone, Liesbet; Clays, Els; Vanaelst, Barbara; Huybrechts, Inge; De Henauw, Stefaan
<x xml:space="preserve">Abstract</x> Objective The public health threats stress and adiposity have previously been associated with each other. Longitudinal studies are needed to reveal whether this association is bidirectional and the moderating factors. Methods In the longitudinal Children's Body Composition and Stress study, 316 children (aged 5–12 years) had measures of stress (questionnaires concerning negative life events, problem behavior, and emotions) and adiposity (body mass index, waist-to-height ratio, and fat percentage) in three waves at 1-year intervals. The bidirectionality of the association between stress and adiposity was examined using cross-lagged analyses. We tested moderation by cortisol and life-style (physical activity, screen time, food consumption, eating behavior and sleep duration). Results Adiposity (body mass index: β = 0.48 and fat percentage: β = 0.18; p < .001) were associated with subsequent increased stress levels, but stress was not directly related to subsequent increases in adiposity indices. Cortisol and life-style factors displayed a moderating effect on the association between stress and adiposity. Stress was positively associated with adiposity in children with high cortisol awakening patterns (β = 0.204; p = .020) and high sweet food consumption (β = 0.190; p = .031), whereas stress was associated with lower adiposity in the most active children (β = −0.163; p = .022). Conclusions Stress is associated with the development of children's adiposity, but the effects depend on cortisol levels and life-style factors. This creates new perspectives for multifactorial obesity prevention programs. Our results also highlight the adverse effect of an unhealthy body composition on children's psychological well-being.